Operating Income and Firm Value: One of Subtotal Income Mandatory IFRS 18 and PSAK 118 - Nur Rahmanti Ratih; Marhaendra Kusuma (Fakultas Ekonomi Universitas Kadiri, 2026)
https://docs.google.com/document/d/1RCyTZciyA719Bs1g42vb0bH3-P7a2UC_/edit?usp=sharing&ouid=105310032583039204129&rtpof=true&sd=true